The Socio-cultural and ecological perspectives on landscape and gardening in Urban Environment: A narrative review - Patrick Chukwuemeke Uwajeh; Ikenna Stephen Ezennia (Journal of Contemporary Urban Affairs, 2018)
This review offers a perspective on the role landscape and gardening play in urban settings from a socio-cultural, and ecological dimension. The practice of cultivating in gardens, parks and vacant lots, creates community spaces, and are increasingly becoming important to peoples’ experience of social and cultural wellbeing. In recent times, this has become a major focus of research in ecology, agriculture, urban design, landscape architecture, human geography, and sociology. Community gardening is one of the avenues toward revitalizing urban environments, and it provides a way of addressing multi-faceted urban problems ranging from limited food access to safety and community cohesion. That being said, it is necessary to continually evaluate the roles which society, ecology, and culture play in cities and landscape planning due to the dynamic nature of culture. This article aims to bring to the fore, the various factors of landscape and gardening practices in cities and the dynamics of cultural and ecological effects they have in building communities, reclaiming communities or engendering a personal place to thrive. A narrative review of the literature on peer-reviewed articles within the scope of the study was adopted as the research method.